ORIENTATION OF THE FUTURE DESIGNERS OF THE BOOK TO A SELF-ESTIMATION O F PROFESSIONAL COMPETENCE AS A CONDUCTING CONDITION OF PREPARATION OF EXPERTS IN HIGH SCHOOLS. (Pedagogy of Higher and Secondary Education, 2007)
The article to the issue of devoted to the future book-designers' guidance for the professional competence self-appraisal as a leading term of the specialists' training in the institutes of higher education. Such a training contributes to the reflexive position development of the future specialists in book-design, what in it’s turn influences the students' critical analysis and constructive perfection of their professional competence level. Thus, a progressive correlation of the students' knowledge about themselves in the context «I am a student» and «I am a competent specialist» forms a life philosophy of the future book-designers, the public value of themselves is being realized. The subject develops its personality in balance, inventively realizing.
Keywords: professional competence; se lf estimation; designer of the book